2000
DOI: 10.1074/jbc.m006633200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of Inhibitors of Bacterial Two-component Signal Transduction Systems

Abstract: Two-component signal transduction systems allow bacteria to sense and respond rapidly to changes in their environment leading to specific gene activation or repression. These two-component systems are integral in the ability of pathogenic bacteria to mount and establish a successful infection within the host and, consequently, have been recognized as targets for new antimicrobial agents. In this paper, we define the site and mechanism of action of several previously identified inhibitors of bacterial two-compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(114 citation statements)
references
References 23 publications
5
97
0
12
Order By: Relevance
“…However, when tested for their antimicrobial potential in vivo, most of these compounds were not selective for signal transduction pathways, but exerted their effects through multiple mechanisms of action (35), making them unsuitable for any clinical application. Most of these inhibitors were developed by random screening, and most of them were shown to bind to the kinase domain, which might explain their restricted selectivity (36). In this study, we demonstrate that an HPK can be inhibited by structural analogues that behave as antagonists.…”
Section: Ortho-substitutions Of Toluene: Converting An Agonist Molecumentioning
confidence: 86%
“…However, when tested for their antimicrobial potential in vivo, most of these compounds were not selective for signal transduction pathways, but exerted their effects through multiple mechanisms of action (35), making them unsuitable for any clinical application. Most of these inhibitors were developed by random screening, and most of them were shown to bind to the kinase domain, which might explain their restricted selectivity (36). In this study, we demonstrate that an HPK can be inhibited by structural analogues that behave as antagonists.…”
Section: Ortho-substitutions Of Toluene: Converting An Agonist Molecumentioning
confidence: 86%
“…6,28,29 However, the majority of these inhibitors suffer from excessive protein binding and/or limited bioavailability and have multiple mechanisms of action including bacterial membrane-damaging and surfactant properties 25 and structural alterations of the histidine kinases leading to aggregation. 30 Therefore, these compounds were not as selective as was originally thought and did not exhibit a strong correlation between their IC 50 s against 2-component systems and minimum inhibitory concentration against bacteria. 6,28 Nonspecific interaction of the compounds with proteins unrelated to their molecular target has been suggested as a possible explanation 31 in addition to aggregate formation leading to nonspecific inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, DNase I can degrade the extracellular DNA present in the biofilm matrix (Okshevsky et al 2015;Qin et al 2007), interfering with its formation and stability as shown for Bordetella pertussis (Conover et al 2011), Listeria monocytogenes (Harmsen et al, 2010), and Campylobacter jejuni (Brown et al 2015). A bacterial glycoside hydrolase, named Dispersin B, has been isolated from Actinobacillus actinomycetemcomitans, which was shown to disrupt mature Actinobacillus biofilms (Rasko et al 2008;Stephenson et al 2000;Wilke et al 2015;Worthington et al 2013). One prominent example is the small molecular inhibitor Savirin, which reduces the expression of AgrCA-regulated genes in S. aureus, affecting its virulence, but not its survival and has no impact on the commensal Staphylococcus epidermidis (Sully et al 2014).…”
Section: Prevention and Resolution Of Biofilmsmentioning
confidence: 99%